Comparing border digitisation and transparency in the EU and Australia - Louis Everuss; Alycia Millar (Australian and New Zealand Journal of European Studies)
Governments are increasingly investing in advanced digital technologies to improve the efficiency and security of their sovereign borders. Research examining this trend has emphasised how digital technologies are reshaping the operation of sovereign borders, but few studies have compared the differing ways that legal contexts influence digital bordering technologies. This article undertakes such an analysis by studying two contexts in which governments are enthusiastically engaging in border digitisation: Australia and the European Union (EU). Our analysis is informed by materialist and science and technology studies (STS)-influenced understandings of the law, which positions legal instruments not as restrictive frameworks that are external to socio-material contexts, but as an embedded part of them. From this perspective, we suggest that there are noteworthy differences in how the legal instruments developed about digital border systems in the EU and Australia are potentially contributing to the production of those systems. In particular, we argue that the EU’s legal instruments are far more conducive to the enactment of transparent digital border systems compared to those deployed in Australia.